PENGARUH KONSENTRASI EKSTRAK CACING TANAH (Lumbricus rubellus)TERHADAP PERTUMBUHAN BAKTERI Salmonella typhi - soedjoto, soedjoto (Universitas Muhammadiyah Surabaya)
PENGARUH KONSENTRASI EKSTRAK CACING TANAH (Lumbricus rubellus)TERHADAP PERTUMBUHAN BAKTERI Salmonella typhiÂ L.Soedjoto,S.SiProdi D3 Analis Kesehatan UM SurabayaÂ AbstractEarthworms (Lumbricus rubellus) is one organism that is widely used as a traditional medicine. Earthworms contains very high levels of protein, enzyme, collagenase enzyme, enzyme Fibrionolycin and Prottibinolycin and seyawa class of alkaloids that contain nitrogen atoms that are bakteriostatik.Berdasarkan description above research was conducted by taking issue with the influence of earthworms and this study aims to determine the effect on growth Salmonella typhi. This type of research is experimental with 10 treatments with a large sample from each treatment was 3, which is drawn at random (random) .. The research was conducted at the Center for Research and Industrial consultancy Laboratory (BPKI) Surabaya in June 2012. Bacterial growth was observed by observing turbidity earthworms in each sample and confirmed by cultivation on media MC (Mac Conkey). The results showed that the concentration of 100% earthworms. 90%, 80%, 70%, 60%, 50%, 40%, 30% showed no growth of Salmonella typhi. While at a concentration of 20%, 10% showed a growth of Salmonella typhi. Chi-square test results showed that the mean value of p = 0.01 p <(0.05). It concluded there was an effect of earthworms on the growth of Salmonella typhi.Keyword : Earthworms (Lumbricus rubellus),Â Salmonella typhi